PENGARUH PERPUTARAN MODAL KERJA, PERPUTARAN PIUTANG, PERPUTARAN TOTAL ASET TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rekno, Heny Purbo; Suhendro, Suhendro; Dewi, Riana Rachmawati (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
This study aim to determine the effect partial and simultaneous working capital turnover, receivable turnover and total asset turnover against profitability used return on asset in manufacturing company listed in Indonesia Stock Exchange in 2015 - 2017. Determination of the sample was done by purposive sampling method. The analysis technique used is regression analysis panel data by determine the common effect, fixed effect, and random effect user computer program software E Views 11. The result show that working capital turnover partially have no significant effect on profitability. Receivable turnover and total assets turnover partially have significant effect on profitability. Simultaneously working capital turnover, receivable turn over, total assets turnover have significant effect on profitability.